Electronic-Based Government System to Digital Government: Strategies and Challenges for Strengthening Digital Public Services in Yogyakarta Province in 2026 - Syaefullah; Dwi Putri Yuliani (Lembaga Bale Literasi, 2026)
Digital transformation in government has become a strategic agenda to improve the quality of public services through the utilization of information and communication technology. The Electronic-Based Government System (SPBE) serves as the main foundation in encouraging the transition from e-government toward a more integrated digital government. This study aims to analyze the strategies, challenges, and transformation model of SPBE toward digital government in the Provincial Government of the Special Region of Yogyakarta. This research applied a qualitative approach with a case study method. Data were collected through interviews, observation, and documentation, then analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing. The results showed that SPBE transformation in Yogyakarta occurred through administrative digitalization using SISMINKADA, system integration through SRIKANDI, and the development of integrated digital public services. The discussion revealed that the main challenges of digital transformation include system integration, data interoperability, human resource readiness, information security, and bureaucratic cultural change. This study develops an SPBE transformation model based on technological integration, organizational capacity, data governance, and user orientation. The study concludes that successful digital government requires systemic transformation that focuses not only on technology but also on strengthening a sustainable digital governance ecosystem.